The Coordination Exercises For Developing Neuromuscular Speed of Response and Compound Skill From Reception to Scoring In Football Players Aged 17 Years Old - Ghazi, Safaa; Saleh, Hamid (Journal of Physical Education, 2019)
Speed of performing compound skills in football is very vital in enabling the player from performing his skills and tactics during the match in spite of having a near opponent due to the strong correlation between coordination in neuromuscular response. The importance of the research lies in conducting a scientific study by giving coordination exercises for developing speed of neuromuscular response speed. The research was applied on (10) football players aged 17 years old from Al Saliekh sport club. The main experiment was applied on 2/6/2019 till 3/8/2019 with three training sessions per week for eight week making a total of twenty four weeks. The coordination exercises were applied in the main part of the session for 30 – 40 minutes. The data was collected and treated using proper statistical operations to come up with the conclusion and recommendations.